2016
DOI: 10.1103/physrevapplied.5.014003
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Selective Switching of a Double-Layer Perpendicular Magnetic Nanodot Using Microwave Assistance

Abstract: Layer-selective manipulation of magnetization direction in a multilayer magnetic structure offers a way to develop a large-capacity magnetic recording device with multiple recording layers. Here, we use a double-layer perpendicular magnetic nanodot consisting of two layers with low and high perpendicular magnetic anisotropy (PMA) and show that layer-selective magnetization switching can be accomplished by utilizing a microwave-assisted magnetization switching technique. Since the low-and high-PMA magnetic laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This leads to a dispersion of the magnetic properties, which strongly affects the switching mechanism when the dimension of the nanostructures becomes smaller. In particular, this has been extensively shown for the switching process of magnetic dots [13,14,15,16,17,18]. When the size of the dots is sufficiently large, the dominant mechanism for switching has been found to be nucleation followed by rapid propagation of magnetic domain walls (DWs).…”
Section: Introductionmentioning
confidence: 94%
“…This leads to a dispersion of the magnetic properties, which strongly affects the switching mechanism when the dimension of the nanostructures becomes smaller. In particular, this has been extensively shown for the switching process of magnetic dots [13,14,15,16,17,18]. When the size of the dots is sufficiently large, the dominant mechanism for switching has been found to be nucleation followed by rapid propagation of magnetic domain walls (DWs).…”
Section: Introductionmentioning
confidence: 94%
“…It was also shown that the magnetization dynamics, such as switching and auto-oscillation, can be excited by spin transfer effect [18] in nanostructured ferromagnetic multilayers [19]. In these dynamic states, several ferromagnets located close to each other within a nanoscale distance affect each other and show a coupled motion of the magnetizations, such as a resonant switching and synchronized oscillation, through stray (dipole) fields from each ferromagnet [20,21,22,23,24,25,26,27,28,29,30,31,32]. Such magnetization dynamics and/or cooperative phenomena are useful for practical applications such as high-density magnetic recording, microwave generators, and neuromorphic architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of FMR excitation can provide novel techniques for manipulating magnetization direction. One is layer-selective MAS, which has been explored as a writing method for multilayer recording 7 , 8 . When a multilayer magnetic structure with each layer having a different FMR frequency is used, switching of only a target layer can be selectively induced by tuning the frequency of the microwave field.…”
Section: Introductionmentioning
confidence: 99%